Intestinal metaplasia in Barrett's oesophagus may be an epiphenomenon rather than a preneoplastic condition, and CDX2‐positive cardiac‐type epithelium is associated with minute Barrett's tumour1. Issue 2 (10th November 2014) - Watanabe, Gen; Ajioka, Yoichi; Takeuchi, Manabu; Annenkov, Alexey; Kato, Takashi; Watanabe, Kaori; Tani, Yusuke; Ikegami, Kikuo; Yokota, Yoko; Fukuda, Mutsumi
<x xml:space="preserve">Abstract</x> Aims Although intestinal‐type epithelium in Barrett's oesophagus has been traditionally recognized as having a distinct malignant potential, whether this also holds true for cardiac‐type epithelium remains controversial. The aim of this study was to identify a type of epithelium that is highly associated with Barrett's tumour. Methods and results We analysed tumours and the corresponding background mucosa with special regard to tumour size in 40 cases of superficial Barrett's tumour by using immunohistochemical staining for CDX2, CD10, MUC2, MUC5AC, and MUC6. Intestinal metaplasia in tumour‐adjacent mucosa was not associated with tumour size, but was significantly correlated with the extent of Barrett's oesophagus (P < 0.001). The majority (69.2%, 9/13) of small tumours (≤10 mm) had no intestinal metaplasia in adjacent non‐neoplastic mucosae. Minute (≤5 mm) tumours were significantly associated with a gastric immunophenotype (P < 0.001). Purely gastric‐immunophenotype tumour cells expressed CDX2, and cardiac‐type epithelium adjacent to small tumours also showed low‐level CDX2 expression. Conclusions Our data suggest that intestinal metaplasia in Barrett's oesophagus is an epiphenomenon rather than a preneoplastic condition, and that CDX2‐positive cardiac‐type epithelium is highly associated with minute Barrett's tumour. Further prospective studies are needed to evaluate the risk of malignancy of cardiac‐type epithelium with regard to sub‐morphological intestinalization.